Frontal lobe 1H MR spectroscopy in asymptomatic and symptomatic MAPT mutation carriers. (20th August 2019) - Chen, Qin; Boeve, Bradley F.; Tosakulwong, Nirubol; Lesnick, Timothy; Brushaber, Danielle; Dheel, Christina; Fields, Julie; Forsberg, Leah; Gavrilova, Ralitza; Gearhart, Debra; Haley, Dana; Gunter, Jeffrey L.; et al.
Abstract : Objective: To determine the frontal lobe proton magnetic resonance spectroscopy ( 1 H MRS) abnormalities in asymptomatic and symptomatic carriers of microtubule-associated protein tau ( MAPT ) mutations. Methods: We recruited patients with MAPT mutations from 5 individual families, who underwent single voxel 1 H MRS from the medial frontal lobe at 3T (n = 19) from the Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects (LEFFTDS) Study at the Mayo Clinic site. Asymptomatic MAPT mutation carriers (n = 9) had Frontotemporal Lobar Degeneration Clinical Dementia Rating Sum of Boxes (FTLD-CDR SOB) score of zero, and symptomatic MAPT mutation carriers (n = 10) had a median FTLD-CDR SOB score of 5. Noncarriers from healthy first-degree relatives of the patients were recruited as controls (n = 25). The demographic aspects and 1 H MRS metabolite ratios were compared by use of the Fisher exact test for sex and linear mixed models to account for within-family correlations. We used Tukey contrasts for pair-wise comparisons. Results: Asymptomatic MAPT mutation carriers had lower neuronal marker N-acetylaspartate (NAA)/creatine (Cr) ( p = 0.001) and lower NAA/myo-inositol (mI) ( p = 0.026) than noncarriers after adjustment for age. Symptomatic MAPT mutation carriers had lower NAA/Cr ( p = 0.01) and NAA/mI ( p = 0.01) and higher mI/Cr ( p = 0.02) compared to noncarriers after adjustment for age. Furthermore, NAA/Cr ( p = 0.006) and NAA/mI ( p < 0.001) ratios decreased, accompanied by an increase in mI/Cr ratio ( p = 0.001), as the ages of carriers approached and passed the age at symptom onset. Conclusion: Frontal lobe neurochemical alterations measured with 1 H MRS precede the symptom onset in MAPT mutation carriers. Frontal lobe 1 H MRS is a potential biomarker for early neurodegenerative processes in MAPT mutation carriers.